Electron-Nuclear Energy Sharing in Above-Threshold Multiphoton Dissociative Ionization of H2 - Wu, J.; Kunitski, M.; Pitzer, M.; Trinter, F.; Schmidt, L. Ph. H.; Jahnke, T.; Magrakvelidze, M.; Madsen, C. B.; Madsen, L. B.; Thumm, U.; Dörner, R. (My University, 2013)
We report experimental observation of the energy sharing between electron and nuclei in above-threshold multiphoton dissociative ionization of H2 by strong laser fields. The absorbed photon energy is shared between the ejected electron and nuclei in a correlated fashion, resulting in multiple diagonal lines in their joint energy spectrum governed by the energy conservation of all fragment particles.